Facile one-step fabrication of all cellulose composites with unique optical performance from wood and bamboo pulp. (15th November 2021) - Hu, Yucheng; Hu, Fuqiang; Gan, Meixue; Xie, Yimin; Feng, Qinghua
Abstract: Cellulosic substrates completely originating from biomass have gained increasing attention for utilization in photoelectric devices due to their biodegradability, sustainability, and renewability. Herein, a simple one-step strategy was used to fabricate transparent (84.2%–90% at 550 nm) all-cellulose composites (ACCs) with customized optical haze (14.7%–83.7% at 550 nm) from wood and bamboo pulp due to their variable solubility. Surface roughness, coagulation bath composition, and the size of the undissolved cellulose fibers contributed to optical haze regulation. Fabricated ACCs demonstrated water resistance, thermal stability, and good mechanical properties. Moreover, an enhancement in the power conversion efficiency of a perovskite solar cell was achieved by simple attachment. Compared with non-sustainable petroleum base materials, ACCs exhibit biodegradability and renewability, which makes the composites promising in large-scale production and various applications due to their tunable haze. Graphical abstract: Unlabelled Image Highlights: All cellulose composites were rapidly obtained via a simple one-step strategy. The structures were revealed via XPS and Raman spectroscopy. Transparent all-cellulose composites exhibit customized optical haze. All cellulose composites could be applied to solar cells and electronic devices.